Variant Location Is a Novel Risk Factor for Individuals with Arrhythmogenic Cardiomyopathy Due to a Desmoplakin (DSP) Truncating Variant - Hoorntje, Edgar T.; Burns, Charlotte; Marsili, Luisa; Corden, Ben; Parikh, Victoria N.; Te Meerman, Gerard J.; Gray, Belinda; Adiyaman, Ahmet; Bagnall, Richard D.; Barge-Schaapveld, Daniela Q.C.M.; Van Den Berg, Maarten P.; Bootsma, Marianne; et al. (Lippincott Williams & Wilkins, 2023)
Background: Truncating variants in desmoplakin (DSPtv) are an important cause of arrhythmogenic cardiomyopathy; however the genetic architecture and genotype-specific risk factors are incompletely understood. We evaluated phenotype, risk factors for ventricular arrhythmias, and underlying genetics of DSPtv cardiomyopathy. Methods: Individuals with DSPtv and any cardiac phenotype, and their gene-positive family members were included from multiple international centers. Clinical data and family history information were collected. Event-free survival from ventricular arrhythmia was assessed. Variant location was compared between cases and controls, and literature review of reported DSPtv performed. Results: There were 98 probands and 72 family members (mean age at diagnosis 43±8 years, 59% women) with a DSPtv, of which 146 were considered clinically affected. Ventricular arrhythmia (sudden cardiac arrest, sustained ventricular tachycardia, appropriate implantable cardioverter defibrillator therapy) occurred in 56 (33%) individuals. DSPtv location and proband status were independent risk factors for ventricular arrhythmia. Further, gene region was important with variants in cases (cohort n=98; Clinvar n=167) more likely to occur in the regions resulting in nonsense mediated decay of both major DSP isoforms, compared with n=124 genome aggregation database control variants (148 [83.6%] versus 29 [16.4%]; P<0.0001). Conclusions: In the largest series of individuals with DSPtv, we demonstrate that variant location is a novel risk factor for ventricular arrhythmia, can inform variant interpretation, and provide critical insights to allow for precision-based clinical management.
Keywords: cardiomyopathies; death, sudden cardiac; desmoplakins; genetic testing; primary; Genetics; Cardiology and Cardiovascular Medicine; Genetics(clinical)